PENINGKATAN AKTIVITAS DAN HASIL BELAJAR SISWA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW PADA MATA PELAJARAN BUDAYA ALAM MINANGKABAU DI SMP NEGERI 2 PULAU PUNJUNG KABUPATEN DHARMASRAYA - KH, YUSNIMAR; Adriani, Adriani; Nelmira, Weni (Journal of Home Economics and Tourism, 2014)
The purpose of this research is to know the improving studentsactivity and their result at Budaya Alam Minangkabau subject by usingcooperative Jigsaw at SMP Negeri 2 Pulau Punjung KabupatenDharmasraya.There are two cycles in this classroom action research.Each cycles needs three meeting and four steps. They are planing, acting,observing and reflecting. It is use to get improvement to next cycles. Theinstrument used to collect data is observation sheets, test, and field notes.The collection of data is helped by an observer. The data is analyzedthrough two ways. Qualitative data is analyzed with narration andargumentation and quantitative data. It must reach 85 % for students’activity. The result of research reaches 87%. The student achievement is85%. The students get score 76. The result of this research is 88%. So, itcan be concluded that using jigsaw cooperative learning model toincrease students’ activity and their result of Budaya Alam Minangkabausubject at students of SMP Negeri 2 Pulau Punjung KabupatenDharmasraya.Keyword: students’ activity, the result, jigsaw coopertive learning model